Criteria and Indicators for Assessing Environmental Performance - qizi, Kobulova Barno Bakhriddin; Orifovna, Sodiqova Zarina (American Journal of Biology and Natural Sciences, 2025)
Environmental efficiency is a core concept in sustainable development, environmental economics, and green growth policy. It reflects the capacity of economic systems, organizations, and technologies to generate value while minimizing pressure on the environment. This article provides a comprehensive scientific analysis of the criteria and indicators used to assess environmental efficiency. Drawing on international methodologies, standards, and academic literature, the study develops a structured system of indicators applicable at micro-, meso-, and macro-levels. The results demonstrate that environmental efficiency assessment requires an integrated, multi-criteria approach combining resource productivity, emission intensity, waste management performance, and ecosystem impact indicators. The proposed framework contributes to improving the analytical basis for environmental policy design and sustainability-oriented decision-making.